Selective oxidation of 5-hydroxymethylfurfural into 2, 5-diformylfuran over VPO catalysts under atmospheric pressure. Issue 25 (7th May 2019) - Lai, Jinhua; Liu, Kai; Zhou, Shuolin; Zhang, Du; Liu, Xianxiang; Xu, Qiong; Yin, Dulin
Abstract : Vanadium phosphate oxide (VPO) heterogeneous catalysts with different V/P molar ratios were prepared. VPO exhibited highly selective oxidation of HMF. The highest DFF yield of 83.6% was obtained under atmospheric air pressure. Abstract : Vanadium phosphate oxide (VPO) heterogeneous catalysts with different V/P molar ratios were prepared and used for selective oxidation of biomass-derived 5-hydroxymethylfurfural (HMF) to produce 2, 5-diformylfuran (DFF) in the liquid phase. It was found that the VPO catalyst with V/P molar ratio 0.25 exhibited the best catalytic performance. Then the VPO catalyst was utilized to catalyze the oxidation of HMF in a batch reactor under different conditions, in terms of type of solvent (water and organic), reaction time and temperature. A high DFF yield of 83.6% with HMF conversion of 100% was obtained under atmospheric pressure.